Self-healing behaviour of lignin-containing epoxidized natural rubber compounds - Bedriye Nur Yeşil; Tuba Ünügül; Bağdagül Karaağaç (eXPRESS Polymer Letters, 2023)
Epoxidized natural rubber (ENR) is a relatively new raw material that can be used in many applications, such as rubber-based adhesives, self-crosslinking, and compatibilization of rubber and filler matrices in favor of reactive epoxy groups. However, as almost all types of polymeric materials do, ENR is exposed to mechanical, chemical, and thermo-oxidative degradation during service life, resulting in micro- and macro-cracks in the material body as well as on the surface. The self-healing approach is considered a good solution to provide longer service life by instantaneous repairing these cracks by means of internal and external stimulants. In literature, most attempts at self-healing of ENR focus on irreversible covalent bond based systems. In this study, lignin and a common anti-reversion agent 1,3-bis(citraconimido-methyl) benzene (CIMB) have been evaluated for carrying out self-healing through reversible covalent bonds via Diels-Alder interaction between ENR and CIMB. In addition, lignin could significantly improve self-healing by promoting an epoxy ring-opening reaction on the ENR backbone. The best healing conditions were selected as 180 °C and 15 minutes, and 83% self-healing was achieved by incorporating 6 phr lignin and 15 phr CIMB into the reference compound. Satisfactory self-healing performance has been attributed to the synergistic effect of lignin and CIMB.